1997
DOI: 10.1103/physrevlett.78.2216
|View full text |Cite
|
Sign up to set email alerts
|

Schwinger-Boson Approach to Quantum Spin Systems: Gaussian Fluctuations in the “Natural” Gauge

Abstract: We compute the Gaussian-fluctuation corrections to the saddle-point Schwinger-boson results using collective coordinate methods. Concrete application to investigate the frustrated J1 −J2 antiferromagnet on the square lattice shows that, unlike the saddle-point predictions, there is a quantum nonmagnetic phase for 0.53 < ∼ J2/J1 < ∼ 0.64. This result is obtained by considering the corrections to the spin stiffness on large lattices and extrapolating to the thermodynamic limit, which avoids the infinite-lattice … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
93
0
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(109 citation statements)
references
References 22 publications
11
93
0
4
Order By: Relevance
“…On the other hand, the Gaussian corrected spin stiffness is obtained by deriving E F L once the twisted mean-field parameters are plugged in Eq. (22). Coming from the isotropic case J = 1 the Gaussian corrections for the spiral phases tend to weaken the spin stiffness until the ground state becomes unstable at J c = 0.43, in accordance with Fig.…”
Section: Schwinger Boson Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, the Gaussian corrected spin stiffness is obtained by deriving E F L once the twisted mean-field parameters are plugged in Eq. (22). Coming from the isotropic case J = 1 the Gaussian corrections for the spiral phases tend to weaken the spin stiffness until the ground state becomes unstable at J c = 0.43, in accordance with Fig.…”
Section: Schwinger Boson Resultssupporting
confidence: 87%
“…To avoid them we introduce the Fadeev-Popov trick which restricts the integration to field fluctuations orthogonal to the gauge orbit 22 . This procedure gives the following Gaussian correction of the free energy:…”
Section: B Gaussian Fluctuationsmentioning
confidence: 99%
“…In fact, Gazza et al 11 performed a Schwinger boson mean field theory and found a continuous transition from collinear to spiral phases at η = 0.375 but with a nonvanishing magnetization m 0 ∼ 0.175. However, inclusion of gaussian fluctuations in this theory would tend to decrease the order, as it is known to occur in highly frustrated cases 12,3 , reaching probably more accord with our spin wave results. The same happens with both theories in the J 1 − J 2 model on a square lattice 13,14,12 .…”
supporting
confidence: 88%
“…In the literature a large number of theoretical studies on systems with antiferromagnetic (AFM) J 1 and J 2 exist. [3][4][5][6][7][8][9][10][11][12][13][14] Here the J 1 -J 2 model 3-14 reveals several interesting magnetic ground states involving quantum phase transitions, such as (i) for α (=|J 2 / J 1 |) 0.4, a Néel AFM state [Q = (π π)], (ii) for α∼0. 4-0.6, a quantum spin-liquid state, and (iii) for α 0.6, an ordered collinear AFM state [Q = (π 0) or (0 π )], i.e., AFM coupling of ferromagnetic (FM) chains in a given plane (by disorder stabilization).…”
Section: Introductionmentioning
confidence: 99%